IMMUNOPATHOGENESIS OF PSORIASIS AND PSORIATIC ARTHRITIS AND PHARMACOLOGICAL PERSPECTIVES - A. Genovese; G.C. Marone; F. Ayala; S. Loffredo; G. Marone (PAGEPress Publications, 2011)
Psoriasis and psoriatic arthritis are chronic inflammatory disorders resulting from a combination of genetic and environmental factors, though the precise causal agents have not yet been identified. The immune system has a major role in their development and the possibility exists that self antigens or antigens from microbial agents, or microbial superantigens initiate a vigorous immune response. Different subsets of T-lymphocytes and dendritic cells, mast cells and granulocytes participate in the pathogenesis and several cytokines and chemokines have been identified in tissue lesions. TNF-α is a key proinflammatory cytokine with important pathogenetic role in psoriasis and psoriatic arthritis. Evidence from clinical trials targeting the TNF-α-TNF-α-receptor supports a central role for this cytokine in the pathogenesis of psoriasis and psoriatic arthritis. Angiogenesis is a prominent early event in lesional psoriatic skin and in synovial membrane psoriatic arthritis. Future potential targets in the treatment of these disorders include biologic agents aimed at blockade of other cytokines, chemokines and angiogenic factors. Key words: Psoriasis, psoriatic arthritis, immunity